Triggering receptor expressed on myeloid cells-1 (TREM-1): a new player in antiviral immunity? - Roe, Kelsey; Gibot, Sébastien; Verma, Saguna (Frontiers in Microbiology, 2014)
The triggering receptor expressed on myeloid cells (TREM) family of protein receptors is quickly emerging as a critical regulator of a diverse array of cellular functions including amplification of inflammation. Although the ligand(s) for TREMs have not yet been fully identified, circumstantial evidence indicates that danger- and pathogen-associated molecular patterns (DAMPs and PAMPs) can induce cytokine production via TREM-1 activation. The discovery of novel functions of TREMs such as regulation of T cell proliferation and activation of antigen presenting cells suggests a larger role of TREM proteins in modulation of host immune responses to microbial pathogens such as bacteria and fungi. However, the significance of TREM signaling in innate immunity to virus infections and underlying mechanisms remains largely unclear. The nature and intensity of innate immune responses, specifically production of type I Interferon and inflammatory cytokines is a crucial event in dictating recovery versus adverse outcome of virus infections. In this review, we highlight the emerging roles of TREM-1, including synergy with classical pathogen recognition receptors. Based on the literature using viral PAMPs and other infectious disease models, we further discuss how TREM-1 may influence host-virus interactions and viral pathogenesis. A deeper conceptual understanding of the mechanisms associated with pathogenic and/or protective functions of TREM-1 in antiviral immunity is essential to develop novel therapeutic strategies for the control of virus infection by modulating innate immune signaling.